Multi-Scale Dynamic Graph Learning for Time Series Anomaly Detection (Student Abstract) - Jin, Yixuan; Wei, Yutao; Cheng, Zhangtao; Tai, Wenxin; Xiao, Chunjing; Zhong, Ting (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
The success of graph neural networks (GNNs) has spurred numerous new works leveraging GNNs for modeling multivariate time series anomaly detection. Despite their achieved performance improvements, most of them only consider static graph to describe the spatial-temporal dependencies between time series. Moreover, existing works neglect the time and scale-changing structures of time series. In this work, we propose MDGAD, a novel multi-scale dynamic graph structure learning approach for time series anomaly detection. We design a multi-scale graph structure learning module that captures the complex correlations among time series, constructing an evolving graph at each scale. Meanwhile, an anomaly detector is used to combine bilateral prediction errors to detect abnormal data. Experiments conducted on two time series datasets demonstrate the effectiveness of MDGAD.